Contextualizing openness: Situating open science - Leslie Chan; Angela Okune; Becky Hiillyer; Denisse Albornoz; Alejandro Reyes Posada (University of Ottawa Press, 2019)
Contextualizing Openness offers a fascinating look at Open Science and the democratization of knowledge in international development and social transformation with a focus on the Global South. This volume presents contributions from the 12 projects that form the Open and Collaborative Science in Development Network (OCSDNet) organized around four central themes: Defining Open Science in Development, Governing Open Science, Negotiating Open Science, and Expanding Open Science for Social Transformation. The collective goal is to illustrate how the opportunities and challenges associated with openness vary across regions and, further, to identify the key differences that characterize the actors, institutions, as well as the infrastructure and governance of knowledge-based resources in highly diverse settings. To understand the movement toward Open Science and its impact on the thinking and practices that drive development, we must challenge the asymmetry of global knowledge production and of access to this knowledge. Contextualizing Openness aims to stimulate further research and debates about how to collectively design a knowledge system that is open and equitable for all.
hdl:10393/39849
Keywords: 320